Need for a Novel Paradigm in Forestry Research: Perspectives of Comparative Atmospheric Cooling Effect by Different Forestry Tree Species - Gupta, S. K.; Singh, Hukum; Ram, Jeet (Indian Forester, 2019)
Trees and forests are a vital component of ecology and the environment. Planting trees are commonly practiced for modulating the environment such as producing shade and cooling as well as reducing air and noise pollution. Different tree species create microclimate under their crowns in comparison to the outside ambient atmosphere with qualitative variations depending upon their structural and anatomical features of leaves in the crown along with their physiological performances. Cooling produced by tree species may be viewed in two aspects viz. local cooling and environment cooling. For local cooling, a leaf may be considered as a thin plate having a certain absorptance to radiant heat. On the other hand, trees soak greenhouse gases present in the atmosphere and modulate the environment. The present article proposes to consider both structural and physiological factors and categorize species according to their effectiveness in producing coolness in the atmosphere. Science, including plant science, is not static and constantly applies new concepts to discover unrevealed facts.